2020
DOI: 10.1177/2516865720910155
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Ten-Eleven Translocation 1 in Epigenetic Responses to Environmental Exposures

Abstract: Mounting evidence from epidemiological studies and animal models has linked exposures to environmental factors to changes in epigenetic markers, especially in DNA methylation. These epigenetic changes may lead to dysregulation of molecular processes and functions and mediate the impact of environmental exposures in complex diseases. However, detailed molecular events that result in epigenetic changes following exposures remain unclear. Here, we review the emerging evidence supporting a critical role of ten-ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 87 publications
0
18
0
Order By: Relevance
“…In recent years, researches on hydromethylation mainly focus on tumors and psychiatric diseases [104,105]. Studies have shown that during organ maturation and drug-induced response, 5hmC analysis can be used as an indicator of cell status and contribute to the identification of toxic carcinogen exposure [106,107]. Dynamic enrichment patterns of methylation and hydromethylation markers may enable us to identify target genes for epigenetic modifications associated with prostate cancer [108].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, researches on hydromethylation mainly focus on tumors and psychiatric diseases [104,105]. Studies have shown that during organ maturation and drug-induced response, 5hmC analysis can be used as an indicator of cell status and contribute to the identification of toxic carcinogen exposure [106,107]. Dynamic enrichment patterns of methylation and hydromethylation markers may enable us to identify target genes for epigenetic modifications associated with prostate cancer [108].…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that CpG methylation of the GAL5.1 enhancer has a significant repressive effect on its activity in SHSY-5Y cells and confirmed previous studies demonstrating the repressive effects of 5mC on regulatory activity. However, our studies could not explore the effects of 5hmC on enhancer activity, which has been associated with increased enhancer activity [38][39][40][41]. Thanks to the recent availability of recombinant TET-proteins, that are able to convert 5mC to 5hmC, it may be possible to compare the effects of 5mC and 5hmC on GAL5.1 action in the near future [44].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an analysis of the effects of 5mC on the ability of 542 transcription factors (TFs) to bind DNA; an essential component of enhancer activation; found that only 23% of TFs experienced reduced binding as a result whereas the binding of 34% of TFs was actually increased by 5mC and the remaining TFs were unaffected [ 37 ]. The role of DNA methylation in influencing enhancer activity is further complicated by the influence of intermediate oxidation products of 5mC; that include 5-hydroxymethyl-cytosine (5hmC), the product of the ten-eleven translocation (TET) dioxygenase enzymes [ 38 ]. 5hmC sites are attractive to transcription factors that activate transcription [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A considerable number of the enzymes participating in regulation of chromatin architecture and gene expression are apparently responsive to environmental cues. Examples are the DNA demethylating ten-eleven translocation methylcytosine dioxygenase (TET), which is up-or downregulated by several environmental factors including food ingredients, ethanol, air pollution and radiation (Zhu et al, 2020), proteins of the Polycomb group that are sensitive to the environmental temperature (Voigt & Kost, 2021), and transcription factors of the TCP family in plants that mediate environmental signals into growth responses (Danisman, 2016). In order to change gene expression, environment-sensitive proteins that are able to modify the epigenetic signatures of the chromatin and DNA must crosstalk with readers of the epigenetic marks and molecules that recruit them to specific sites of the DNA and chromatin (Figure 1).…”
Section: Generation Of Multiple Phenotypes From the Same Genotype By ...mentioning
confidence: 99%